SOSIALISASI KEAGAMAAN MAGHRIB MENGAJI PADA ANAK DI DESA DAMAI KECAMATAN BENGKALIS - Didik Kurniawan; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The phenomenon of children and adolescents equipping religious values is experiencing a shift in the development of the times so that the morality and behavior of children are threatened on deviations and contrary to the values and norms in force. Problems occur in children due to lack of control and supervision in socializing as well as a lack of understanding of children about religious education. This study aims to find out how to socialize and foster the application of the Program from Maghrib Koran activities to children. The location of this research is in the Multipurpose Building, Jl. Utama, Sungai Gelam Hamlet, Damai Village, Bengkalis District. Researchers used descriptive qualitative analysis methods by telling and giving an overview of research results in a systematic and logical manner. The criterion of the research subject is those directly involved in the Koran Maghrib program with a total of 10 people (5 key informants and 5 informants). The analysis uses socialization theory (George Herbert Mead) and symbolic interaction theory (Herbert Blumer) as supporting theories. The results of the study explained that the application of Kaji Maghrib socialization was welcomed and could be accepted in the community. The role of parents in children's religious education is still relatively low. The role of the board or teacher is the key to the success of the activity by applying learning coaching with various methods being taught. During the socialization of activities, experienced a good development. the overall ability of children is categorized as still low in terms of learning. The lack of participation in studying religious teaches ranging from adolescents, adults and parents. Constraints in terms of implementation time are also limited to only 2 meetings held during the week.Keywords: Socialization, Maghrib Reciting, Children